2013
DOI: 10.1134/s1068162013010056
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic method of 1,2,4-triazole nucleoside synthesis: Possibilities and limitations

Abstract: The potentialities and restrictions of chemoenzymatic approach to the synthesis of new structural analogues of antiviral drug Ribavirin (1-beta-D-ribofuranosyl-1,2,4-triazole-3-carboxamide) have been determined. Syntheses of various amides of 1H-1,2,4-triazole-3-carboxylic acid and its 5-substituted analogues, prospective substrates of purine nucleoside phosphorylase (PNP), have been reported. The comparative effectiveness of the methods for obtaining amides aforementioned and also the methods for introducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…It was previously reported that 1,2,4-triazolecarboxylic acid esters are not PNP substrate [20]. Therefore, only 1,2,4triazole-3-carboxamide 8 (TCA) could be used as a free heterocyclic base in Ribavirin synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that 1,2,4-triazolecarboxylic acid esters are not PNP substrate [20]. Therefore, only 1,2,4triazole-3-carboxamide 8 (TCA) could be used as a free heterocyclic base in Ribavirin synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Однако возможны и альтернативные пути фосфорилирования, не связанные с hADK, и другие типы фармакологической активности. В ходе исследования субстратной специфичности генно-инженерной PNP E. сoli [97,98] был получен ряд аналогов рибавирина, N-алкилированных по амидной группе. Как выяснилось, даже объемные заместители в карбоксамидном фрагменте не препятствуют реакции трансгликозилирования, катализируемой PNP (рис.…”
Section: изостерические аналоги по карбоксамидной группеunclassified
“…Выяснилось, что противовирусную активность проявляют не только нуклеозиды или ациклические нуклеозидные аналоги, но и их защищенные производные, и сами гетероциклические основания, у которых активность оказалась максимальна. Предположить в этом случае механизм, включающий синтез нуклеозида из основания с участием PNP, невозможно, так как столь объемный заместитель в 5-ом положении ограничивает субстратную специфичность фермента [97,105]. Остается полагать, что за противовирусную активность отвечает само гетероциклическое основание, а гликозидный фрагмент несет скорее транспортную функцию.…”
Section: аналоги рибавирина замещенные по 5-му положению гетероциклаunclassified
“…Once absorbed into the bloodstream, viramidine is transformed to ribavirin in the liver and doesn't accumulate in erythrocytes, thus lowering the risks of adverse effects associated with anemia. [47] The research and production of all 1,2,4-triazole compounds as antiviral products have been extensively reviewed in the literature published in the last decade via searching in the SciFinder database. The review article consists of three main sections, based on the ligand chemical structure of the 1,2,4triazole nucleus.…”
Section: Introductionmentioning
confidence: 99%